Evaluation of polyphenolic compounds in membrane concentrated pistachio hull extract. (30th March 2019) - Seifzadeh, Negin; Ali Sahari, Mohammad; Barzegar, Mohsen; Ahmadi Gavlighi, Hassan; Calani, Luca; Del Rio, Daniele; Galaverna, Gianni
Highlights: Membrane process was able to separate a fraction rich in polyphenols from PGHE. 34 polyphenolic compounds were identified in pistachio hull extract. Eight polyphenolic compounds reported for the first time in pistachio hulls. Most of the quantified polyphenols accumulated in the retentate of 1 kDa membrane. Rutin accumulated in the retentate part of the 10 kDa membrane. Abstract: Pistachio hull is a substantial source of natural polyphenols, but a substantial volume is being wasted annually. Aqueous pistachio green hull extract (PGHE) was subjected to two-stage membrane process in order to separate a polyphenol rich fraction. The membrane conditions of each stage were investigated. Total phenolic content and antioxidant activity were determined by Folin–Ciocalteu and DPPH · assay; also membrane fouling was monitored. The use of the 1 kDa cellulose membrane accompanied by 4 bar pressure and 250 rpm stirring speed was observed to be successful in the separation of a fraction with the highest amount of phenolic compound and antioxidant activity, in the retentate part. UHPLC/MS n characterization of PGHE polyphenols enabled us to identify 34 compounds, including the most abundant galloylshikimic acids, gallic acid, theogallin, galloyl- O -hexoside, quercetin- O -hexoside and pyrogallol.